Keanekaragaman dan kelimpahan kupu-kupu (Lepidoptera) di Lapangan Watu Gajah Tuban - Sonia, Shela; Jamilah, Yaquta Maziyatin; Azzahra, Athiyya Nur Agistiana; Anissa, Ratih Khairul; Rahayu, Dwi Anggorowati (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Butterflies are insects that belong to the Order Lepidoptera or "scale-winged insects". Butterflies are generally found in green open areas, such as at Watu Gajah Tuban Field. Butterflies are very sensitive to environmental changes which can be seen from changes in the composition of their community. Diversity of butterflies in an environment is a bioindicator of ecological quality in that environment. This study aims to identify and analyze the diversity and abundance of butterfly species found in Watu Gajah Field, Semanding District, Tuban Regency, East Java. The Watu Gajah Field area can be categorized as an environment that supports the life of insects, especially butterflies with an average height of 40 meters above sea level, a temperature of 29 o C, wind speed of 13 km/h, rainfall of 1.9 mm, humidity of 70.33%and light intensity 4259.33 lux. Research using exploratory survey methods (cruising) or direct capture using insect nets using insect nets and hand sampling techniques at 3 observation stations, with each station sampling are 5 times. Data analysis was carried out using the relative abundance formula, the Shannon-Winner diversity index and the Shimpson dominance index. Based on the results of the study, 13 butterfly species were obtained with the diversity index and the butterfly dominance index in Watu Gajah Field, namely the diversity index was classified as moderate, namely 2.32 with an H value of 2.0<H'<3.0. Meanwhile, the dominance index of 0.083 is included in the low category with a value of 0<D<0.5. Watu Gajah Field is an ideal habitat that is more suitable for butterfly development.